Guidelines for using Game Technology as Educational Tools - Damian Schofield (Journal of Education and Learning (EduLearn), 2018)
Advanced three-dimensional virtual environment technology, similar to that used by the film and computer games industry, can allow educational developers to rapidly create realistic online virtual environments. Generic rules of thumb regarding the specification, development, application, and operation of these learning environments can be garnered from industrial training systems and examined in an educational context [1-3]. This paper introduces a virtual learning environment ViRILE (Virtual Reality Interactive Learning Environment) developed by the author. ViRILE is designed for use by undergraduate chemical engineers to simulate the configuration and operation of a polymerisation plant. This paper will also discuss the implementation of this and other similar systems and extrapolate the lessons learnt into general pedagogical guidelines to be considered for the development of VR based online educational learning resources.